2018
DOI: 10.17235/reed.2018.5419/2017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of transoral outlet reduction via endoscopic suturing in patients with weight regain after a surgical Roux-en-Y gastric bypass

Abstract: endoscopic suture reduction of the dilated gastro-jejunal anastomosis and the gastric pouch seems a feasible and safe option in our limited initial experience. With a multidisciplinary approach and a short term follow-up, this seems to be a minimally invasive and effective option to control weight regain after RYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There were also no severe adverse events in either group, demonstrating the safety of this intervention [39]. Subsequent TORe studies have also shown sustained and continued weight loss 3 to 5 years after TORe for weight recurrence after LRYGB [41][42][43]. A 2020 study also found that a modified endoscopic submucosal dissection around the GJA prior to endoscopic suturing increases weight loss compared to the APC-TORe procedure [44].…”
Section: Endoscopic Suturingmentioning
confidence: 87%
“…There were also no severe adverse events in either group, demonstrating the safety of this intervention [39]. Subsequent TORe studies have also shown sustained and continued weight loss 3 to 5 years after TORe for weight recurrence after LRYGB [41][42][43]. A 2020 study also found that a modified endoscopic submucosal dissection around the GJA prior to endoscopic suturing increases weight loss compared to the APC-TORe procedure [44].…”
Section: Endoscopic Suturingmentioning
confidence: 87%
“…It is hypothesized that the weight loss post TORe was secondary to reduction in GJA size, improved eating habits, quicker gastric emptying times, and induction of satiety by stimulating gastric stretch receptors 11 24 27 28 . Weight recidivism was reported to be due to genetic factors, lack of dietary compliance, or due to suture breakage/migration leading to dilation of the GJA after TORe 26 27 28 36 .…”
Section: Discussionmentioning
confidence: 99%
“…However, according to Jirapinyo et al, there was an increased incidence of nausea and vomiting with GJA < 4 mm 37 . The majority of the studies aimed for a GJA size < 10–12 mm 12 23 24 25 26 27 29 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its efficacy, WR after RYGB is an escalating concern ( 11 ). Changes in anatomy, among other factors, have been shown to contribute to this pathology.…”
Section: Roux-en-y Gastric Bypassmentioning
confidence: 99%